2022
DOI: 10.1111/os.13291
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Spinal Ligament Ossification in Patients with Thoracic Myelopathy

Abstract: Objective To evaluate the rate of increase in thickness and cross‐section area (CSA) of the ossification in thoracic myelopathy with or without cervical and lumbar spinal ligament ossification. Methods A total of 24 patients with 170 segments (47 ligamentum flavum [OLF] and 123 cases of ossification of the posterior longitudinal ligament [OPLL]) of spinal ligament ossification between January 2012 and March 2019 at a single institution were retrospectively reviewed. Demographic data, classification of OPLL, Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Hypertrophy of the ligamentum flavum (HLF), which may or may not have accompanying ossification (OLF), can cause SS by compressing the spinal cord, cauda equina, and nerve roots [ 45 ]. As an independent disease, HLF/OLF often occurs in the thoracic spine followed by the lumbar spine [ 46 ]. HLF/OLF causes central stenosis in both the thoracic and lumbar spine regions ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…Hypertrophy of the ligamentum flavum (HLF), which may or may not have accompanying ossification (OLF), can cause SS by compressing the spinal cord, cauda equina, and nerve roots [ 45 ]. As an independent disease, HLF/OLF often occurs in the thoracic spine followed by the lumbar spine [ 46 ]. HLF/OLF causes central stenosis in both the thoracic and lumbar spine regions ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…After the decompression and fusion surgery, the JOA scores at follow-up improved compared with the preoperative condition. However, as the DISH often involved the middle and lower thoracic spine, the responsible lesions were often septal, and thus staged surgery should be performed [ 21 ]. However, DISH has been identified as a risk factor for unanticipated second surgery in patients with lumbar degenerative disease, with a revision rate of up to 19% in DISH patients versus 6.9% in non-DISH patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, QoL and VAS are significantly lower in patients with > 50% spinal canal occupancy on both CT and MRI than in patients with ≤ 50% occupancy, which is consistent with some previous studies that concluded that spinal canal occupancy on MRI showed a significant correlation with anxiety/depression aspects in regression models. 32 Therefore, we still need to care more for patients with severe spinal canal occupancy.…”
Section: Discussionmentioning
confidence: 99%